Does the Mena Countries May Converge in GDP to Southern European One? The Effects of International Trade - Dhrifi, Abdelhafidh; Maktouf, Samir (International Journal of Business, Economics and Management, 2014)
The recent integration of the countries of the MENA region in globalization movement and the signing of the Euro-Med agreements with the European Union has naturally prompted researchers and economists to test the hypothesis of convergence towards the Europe. This paper, which is in this context, tends to test whether movement toward international trade will foster a reduction in the disparity of incomes among countries. More specifically, we try to answer the following question: does international trade allows MENA Countries to converge in GDP per capita to Southern European one, and if this convergence is possible, what is the time required for a developing country to reduce the gap that separates the countries of a developed one? Using time series approach convergence over the period 1990-2011, results shows that the convergence hypothesis is checked for most of the selected countries in the MENA region.Our findings show also that the calculation of the time required for MENA countries to reduce the gap that separates to the Southern European one varies from one country to another.